Regulating the for‐profit private healthcare providers towards universal health coverage: A qualitative study of legal and organizational framework in Mongolia. (29th May 2017) - Tsevelvaanchig, Uranchimeg; Narula, Indermohan S.; Gouda, Hebe; Hill, Peter S.
Summary: Background: Regulating the behavior of private providers in the context of mixed health systems has become increasingly important and challenging in many developing countries moving towards universal health coverage including Mongolia. This study examines the current regulatory architecture for private healthcare in Mongolia exploring its role for improving accessibility, affordability, and quality of private care and identifies gaps in policy design and implementation. Methods: Qualitative research methods were used including documentary review, analysis, and in‐depth interviews with 45 representatives of key actors involved in and affected by regulations in Mongolia's mixed health system, along with long‐term participant observation. Results: There has been extensive legal documentation developed regulating private healthcare, with specific organizations assigned to conduct health regulations and inspections. However, the regulatory architecture for healthcare in Mongolia is not optimally designed to improve affordability and quality of private care. This is not limited only to private care: important regulatory functions targeted to quality of care do not exist at the national level. The imprecise content and details of regulations in laws inviting increased political interference, governance issues, unclear roles, and responsibilities of different government regulatory bodies have contributed to failures in implementation of existing regulations.